Generating Relations by Using Some Classes of Near Open Sets - Iqelan, M. J; Rajab, N. A (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The purpose of this paper is to introduce some definitions of relations generated by using some classes of near open sets in topological spaces. Proved results and examples are provided.